1993
DOI: 10.1111/j.1600-0536.1993.tb03373.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of false‐negative reactions to the fragrance mix

Abstract: To estimate the frequency of false-negative reactions to the fragrance mix, the 8 constituents of the mix in concentrations of 5% (2% for cinnamic aldehyde) were added to the European standard series for routine testing. Patients with positive reactions to individual ingredients in the absence of a reaction to the mix were retested with serial dilutions. In a 4-month period, 677 patients were tested. 61 (9%) reacted to the mix and to 1 or more of the ingredients. 4 patients (0.6% of all patients tested and 6.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 7 publications
(5 reference statements)
0
40
2
Order By: Relevance
“…Previously (90), these authors had found that, of 179 patients suspected of cosmetic allergy, 13 reacted to ingredients of the mix tested at a higher concentration (7Xisoeugenol, 4Xoak moss, 1 X geraniol, and 1 combination), in the absence of a positive reaction to the mix itself. In the more recent study (89), patients with a negative reaction to the mix, but a positive reaction to 1 or more ingredients (5% pet. without SSO, cinnamic aldehyde 2% pet.…”
Section: The Fragrance Mix: Very Useful But Not Idealmentioning
confidence: 95%
See 4 more Smart Citations
“…Previously (90), these authors had found that, of 179 patients suspected of cosmetic allergy, 13 reacted to ingredients of the mix tested at a higher concentration (7Xisoeugenol, 4Xoak moss, 1 X geraniol, and 1 combination), in the absence of a positive reaction to the mix itself. In the more recent study (89), patients with a negative reaction to the mix, but a positive reaction to 1 or more ingredients (5% pet. without SSO, cinnamic aldehyde 2% pet.…”
Section: The Fragrance Mix: Very Useful But Not Idealmentioning
confidence: 95%
“…Of 677 patients tested, 6 had a positive reaction to ingredients, but a negative reaction to the mix. With serial dilution tests, 4 (0.6% of all patients and 6.2% of all fragrance-sensitive patients) had positive reactions to cinnamic alcohol, geraniol, isoeugenol and oak moss, I reaction each, which indicated that false-negative reactions to the mix occurred in them (89). Although these %s are rather small, the authors state that, given the large number of patients allergic to perfumes, several fragrancesensitive patients allergic to ingredients of the mix are missed with the mix of current composition.…”
Section: The Fragrance Mix: Very Useful But Not Idealmentioning
confidence: 99%
See 3 more Smart Citations